Study on pollution of soils due to disposal of pulp mill effluent - Narasinga Rao, B.N.D; Rama Rao, R; Joardar, Dibyatanay (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Rapid industrialization resulted in the generation and disposal of large volumes of solid, liquid and gaseous wastes into the environment. Geotechnical characterization of soils polluted by industrial wastes is an essential aspect of Environmental Geotechniques. The present paper investigates the effect of pulp mill waste on volume change behavior of Bentonite and Kaolinite.Electrolyte concentration of the effluent emerges as the single most important factor influencing the interaction. The considerable increase in the permeability of bentonite treated with the effluent indicates that the extent of pollution would increase to a wider area with time affecting the structures over such soil. The increase in permeability also results ultimately in pollution of ground water resources.The significant decrease in permeability of kaolinite treated with the pulp mill effluent indicates possible drainage problems and consequent pounding up of the effluent at the disposal site, increasing the waste land formation. The paper presents the results of this study. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>